Meeting phenomena of red blood cells in rolls of coins and irregular agglomerates. Sedimentation rate of red blood cells. Blood groups. Techniques. - Ciotola, Enrique (1927)
The first observations of agglutination of red blood cells caused by the serum of animals of other species dates back many years. The agglutination of red blood cells of some individuals, others by sera from the same species, is a recent development. Shattock observed this phenomenon for the first time with human blood.